1971
DOI: 10.1002/app.1971.070150816
|View full text |Cite
|
Sign up to set email alerts
|

Thermal analysis of polymers. VIII. Dilatometric and thermal optical behavior of sulfur

Abstract: SynopsisThe use of combined modes of thermal analysis by differential thermal analysis (DTA), thermomechanical analysis, and thermal depolarization analysis (TDA) presents a more illustrative picture of the phase transitions and behavior of the allotropes of sulfur.Volumetric changes suggest the T, of polymeric sulfur to occur at 35OC. Changes in depolarized light level and an abrupt change in volume a t 77°C identify this change as a firstorder fusion. The depolarized light behavior of sulfur, which has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1975
1975
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…In the work of Ficara and Moreira, there are two endothermic peaks at 108.25 °C and 119.50 °C for the DSC of standard sulfur, which represent the α-sulfur to β-sulfur transition and the melting of sulfur, respectively (Ficara and Moreira, 1988). Their measurement conditions are very close to this study; thus, the first peak at 108.2 °C could be assigned to the transformation of α-sulfur into β-sulfur (Laitinen and Niinisto, 1978;Miller, 1971;Thackray, 1970).…”
Section: Elemental Composition and Mineral Phases In The Leach Residuesupporting
confidence: 75%
“…In the work of Ficara and Moreira, there are two endothermic peaks at 108.25 °C and 119.50 °C for the DSC of standard sulfur, which represent the α-sulfur to β-sulfur transition and the melting of sulfur, respectively (Ficara and Moreira, 1988). Their measurement conditions are very close to this study; thus, the first peak at 108.2 °C could be assigned to the transformation of α-sulfur into β-sulfur (Laitinen and Niinisto, 1978;Miller, 1971;Thackray, 1970).…”
Section: Elemental Composition and Mineral Phases In The Leach Residuesupporting
confidence: 75%
“…Of these, the only thermodynamically-stable polymorphs are orthorhombic c~-sulfur, stable at NTP, and monoclinic/~-sulfur, stable only in the narrow temperature range between 95.4 ~ and its melting point [2]. The stability ranges and other thermal properties of e-and fl-sulfur have also been established by modern thermoanalytical methods [3,4].The third well-known polymorph of cyclo-octasulfur is monoclinic y-sulfur, which has recently been structurally characterized by X-ray diffraction methods [5]. Although y-sulfur itself is not thermodynamically stable relative to the ~-and//-forms, it has been reported that this structure type is found in sulfur crystals containing approximately 10-45~o selenium [6][7][8][9].…”
mentioning
confidence: 97%
“…The monoclinic β-S 8 form exhibits the dominant melt transition at 119 ºC and upon continued heating the molten sulfur undergoes equilibrium polymerization ( Fig. 3) [17][18][19][20][21][22].…”
Section: Polymeric Sulfurmentioning
confidence: 99%